Partial Excision and Ablative Carbon Dioxide Fractional Laser Therapy for Multiple Apocrine Hidrocystomas on the Periorbital Regions and Cheeks - Hiroshi Kitagawa; Isao Sugimoto; Toshinori Bito; Keiichi Yamanaka; Hiroto Terashi (Case Reports in Dermatological Medicine)
A 51-year-old Japanese woman presented with translucent papules on the periorbital area and cheeks that had progressively enlarged over five years. She underwent a skin biopsy and was diagnosed with multiple apocrine hidrocystomas. Her lesions became more pronounced and obscured her vision when her body warmed up, such as during bathing. To alleviate her symptoms, we began treatment by partially resecting the tumors on the lower eyelids. After surgery, her vision was no longer obscured. Approximately 1.5 years later, she underwent ablative 10,600 nm carbon dioxide fractional laser therapy for the mildly enlarged apocrine hidrocystomas on her lower eyelids and cheeks. At roughly six months of follow-up, the symptoms had improved, and the cosmetic results were satisfactory, although minor scarring and hypopigmentation were still evident. These case findings underscore the effectiveness of ablative carbon dioxide fractional lasers in treating apocrine hidrocystomas.